Original paperA cross-sectional study of prevalence and risk factors for childhood asthma in Ahvaz city, Iran - Tavacol, Heshmatollah; Rahimi, Zahra; Cheraghi, Maria; Ghatfan, Fathemeh; Baji, Zahra; Rahmani, Hossein (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Childhood asthma is the main public health problem in world, and dramatically has increased in developed as well as developing countries. Aim : To assess prevalence and risk factors for asthma based on ISAAC questionnaire. Material and methods : It was a cross-sectional school population-based study which was carried out on 1803 school children aged 6–7 and 13–14 in Ahvaz city, Khuzestan, south west of Iran, in 2011. The International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire was used as a tool to identify prevalence of asthma. Chi-square (c2) test was then used to identify possible potential risk factors associated with asthma. Logistic regression analysis was then applied to determine the various potential risk factors associated with asthma. Data were entered and analyzed using SPSS (version 17) statistical analysis software. The significant level in this study was considered 0.05. Results : The overall prevalence of asthma among school children was 4.9%, but in males it was 5.5% and in females – 4.3%. Also findings have demonstrated that prevalence of asthma was higher among 13–14 years age group (6.1%) as compared to children aged 6–7 (3.7%). The prevalence of wheeze in the last 12 months, wheeze after exercise and playing was 18.1%, 13.9%, and 8.4% respectively. Prevalence of dry cough at night was reported in 17.6%. Prevalence of asthma was highest in winter (2.6%). Conclusions : Prevalence of asthma in children was higher in males than females and prevalence of allergic symptoms will be increased with high air pollution. Family history of asthma was a strong risk factor for childhood asthma.